Individualized Homeopathic Medicines in the Treatment of Painful Diabetic Peripheral Neuropathy: A Single-Arm, Pre–Post Comparison Trial - Sanyal, Srimonti; Ghosh, Shubhamoy; Dutta, Abhijit (Homœopathic Links, 2023)
Painful peripheral neuropathy is one of the most common microvascular complications of long-continued, uncontrolled diabetes mellitus. The role of individualized homeopathic treatment has not been well evaluated in managing such cases earlier. This aim of this study was to assess the impact of individualized homeopathic treatment on pain intensity in patients with painful diabetic peripheral neuropathy (PDN) through an open-label, single-arm, pre–post comparison clinical trial. A total of 39 patients diagnosed with PDN were included in the trial. The visual analog scale (VAS) for pain and the 36-Item Short Form Survey (SF-36) were utilized as outcome measures and administered at baseline and after 3 months of intervention. Homeopathic medicines were prescribed using a precision-guided approach based on individualized principles. The changes in VAS score and SF-36 domains were analyzed using the Wilcoxon matched pairs signed rank test. Statistically significant reduction in neuropathic pain (median: 8.0; interquartile range [IQR]: 7.0–9.0) compared with baseline (median: 6.0; IQR: 5.0–7.0) were observed (Z = −5.34; p < 0.001). Moreover, improvements were seen in various SF-36 domains related to physical and emotional well-being, social functioning, pain, general health, and health change after 3 months of treatment. The frequently prescribed medicines included Lycopodium clavatum (15.4%), Natrum muriaticum (15.4%), Causticum (15.4%), Medorrhinum (12.8%), and Sulphur (12.8%). Individualized homeopathic treatment significantly reduced pain and enhanced the quality of life in individuals suffering from PDN. However, further randomized trials with improved methodological rigor are needed to strengthen the conclusions drawn from this study.Trial Registration CTRI/2018/10/016196; UTN: U1111–1221–7664.
Keywords: painful diabetic neuropathy; homeopathy; clinical trial; visual analogue scale; SF-36